Performance of Nordic Stock Assembled ESG Momentum : Comparison to benchmark of MSCI Nordics ESG Universal Index - Karlsson, Mikael (My University, 2023)
The purpose of this study is to evaluate the performance of a Nordic stock assembled ESG mo-mentum strategy that incorporates environmental, social, and governance (ESG) scores in port-folio creation. Three different ESG momentum portfolios are constructed in this study to exam-ine the return characteristics of the portfolios. The returns are analyzed with three different multi-factor portfolio measures to find the best fitting model to explain the returns. The empir-ical part of this study also shows comparison of the returns against the chosen benchmark MSCI Nordics ESG Universal Index. Environmental and social awareness have increased considerably during the 21st century. This increased global awareness has significantly accelerated the global economies to respond accordingly. Relatively new concepts have been invented, corporate be-havior has been changing, stakeholders of companies are requiring continuous sustainability ac-tions from companies, and legislation is changing globally to adjust for modern, more sustaina-ble world. The rapid growth around corporate social responsibility actions have consequently started to increase the amount of socially responsible investments. This study is focusing on one of the most recent socially responsible strategy, the ESG momentum strategy. ESG momentum strategy aims to provide excess returns by buying companies with positive ESG score trend and selling short companies with negative trend. The ESG momentum strategy is modified to ESG context from traditional momentum strategy. Nordic countries are considered to be sustaina-bility leaders in the world, so it could be assumed that the relationship between good ESG per-formance and financial performance would be positive and vice versa especially in the Nordic markets. However, the results of this study do show slightly negative and statistically significant alpha and therefore this study cannot fully support the positive findings of previous studies. The results suggest that ESG ratings alone are not sufficient to predict a company's future financial performance, although the top 10 decile of companies with improved ESG ratings outperformed the benchmark index.

Tämän tutkimuksen tarkoituksena on arvioida pohjoismaisista osakkeista koostetun ESG-mo-mentum strategian suorituskykyä, portfolion rakentamisessa otetaan huomioon ympäristö-, yh-teiskunta- ja hyvä hallintotapa (ESG). Tässä tutkimuksessa rakennetaan kolme erilaista ESG-mo-mentum portfoliota, joiden tuotto-ominaisuuksia tutkitaan. Tuottoja analysoidaan kolmella eri monifaktori mallilla, jotta löydettäisiin parhaiten tuottoja selittävä malli. Tutkimuksen empiiri-sessä osassa vertaillaan tuottoja myös valittuun vertailuindeksiin MSCI Nordics ESG Universal Indexiin. Ympäristötietoisuus ja sosiaalinen tietoisuus ovat lisääntyneet huomattavasti 2000-lu-vulla. Tämä lisääntynyt maailmanlaajuinen tietoisuus on nopeuttanut merkittävästi maailman-talouden reagointia. Uusia käsitteitä on keksitty, yritysten käyttäytyminen on muuttunut, yritys-ten sidosryhmät vaativat yrityksiltä jatkuvia kestävään kehitykseen liittyviä toimia ja lainsää-däntö muuttuu maailmanlaajuisesti mukautuakseen nykyaikaiseen, kestävämpään maailmaan. Yritysten sosiaalisen vastuun nopea kasvu on alkanut lisätä sosiaalisesti vastuullisten investoin-tien määrää. Tässä tutkimuksessa keskitytään yhteen uusimmista sosiaalisesti vastuullisista stra-tegioista, ESG momentum -strategiaan. ESG momentum -strategialla pyritään tuottamaan yli-tuottoa ostamalla yrityksiä, joiden ESG-pisteet kehittyvät positiivisesti, ja myymällä lyhyeksi yri-tyksiä, joiden ESG-pisteiden suuntaus on negatiivinen. ESG momentum -strategia on muunnettu ESG-kontekstiin perinteisestä momentum strategiasta. Pohjoismaiden katsotaan olevan maail-man johtavia kestävän kehityksen maita, joten voidaan olettaa, että hyvän ESG-tuloksen ja ta-loudellisen tuloksen välinen suhde olisi positiivinen ja päinvastoin erityisesti pohjoismaisilla markkinoilla. Tämän tutkimuksen tulokset osoittavat kuitenkin hieman negatiivista ja tilastolli-sesti merkitsevää alfaa, joten tämä tutkimus ei voi täysin tukea aiempien tutkimusten myöntei-siä tuloksia. Tulokset viittaavat siihen, että ESG-luokitukset eivät yksinään riitä ennustamaan yri-tyksen tulevaa taloudellista suorituskykyä, vaikka 10 parasta kymmenesosaa yrityksistä, joiden ESG-luokitukset olivat parantuneet, tuottivatkin paremmin kuin vertailuindeksi.
Keywords: ethical investing; corporate responsibility; investments (economics); sustainable development; finance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance